EFFECTIVENESS OF FLASH FLOOR TO IMPROVE HAIR QUALITY OF KINTAMANI BALI DOGS - Farros, Cita Kanz; Sudira, I Wayan; Samsuri, Samsuri (Buletin Veteriner Udayana, 2023)
Dogs are pets that can easily adapt to humans. The first native Indonesian dog breed recognized by the Indonesian Kinology Association (PERKIN) is the Kintamani dog. Kintamani dogs are unique in their appearance, namely badong hair and gumba hair. Along with increasing public interest in maintaining Kintamani dogs, it is also necessary to pay attention to maintaining dog health. One of them is the health of the Kintamani dog's hair. Kintamani dog hair health can beautify or aesthetic, make the hair healthier and can maintain the health of the dog's skin. Hibiscus is traditionally believed to have activity that can stimulate hair growth, namely from flowers and leaves of hibiscus. The purpose of this study was to determine the effect of giving hibiscus leaves to improve the hair quality of Kintamani dogs. There are 3 parameters observed in this study; hair strength, hair shine, and hair loss of Kintamani dogs. This study used 30 samples of Kintamani dogs and conducted by simple random sampling obtained from dog owners from Bangli Regency, Bali Province. Samples of dogs will be divided into 2 groups, with the division of 15 Kintamani dogs bathed with crushed hibiscus leaves and 15 Kintamani dogs bathed with commercial dog shampoo. After the sample is bathed, a comparison test of the hair quality of the Kintamani dog will be carried out. Giving crushed hibiscus leaves is given once a week for 3 weeks. The test is given 2 hours after the dog is bathed. The test was carried out macroscopically by being carried out once a week for 21 days on the 30 Kintamani dogs. The observed data were then analyzed using the Kruskal walis nonparametric statistical test and continued with the Wilcoxon test. The results showed that there was no significant difference in the hair quality of dogs using hibiscus leaves and commercial dog shampoo ( Natural Septic ).